Magnitude and associated factors of mortality among patients admitted with COVID-19 in Addis Ababa, Ethiopia. - Genanew Kassie Getahun; Amare Dinku; Dube Jara; Tewodros Shitemaw; Zelalem Negash (Public Library of Science (PLoS), 2023)
The COVID-19 pandemic continues to grow around the world and has caused enormous mortality and morbidity. The severity and mortality of coronavirus disease are associated with various comorbidities. The infection fatality rate was reported to be inconsistent with different studies. Therefore, the aim of this study was to assess the magnitude and factors associated with mortality among patients admitted to Eka Kotebe General Hospital, Addis Ababa, Ethiopia. An institutional-based cross-sectional study was conducted at Eka Kotebe General Hospital among patients who were admitted for COVID-19 from January 15, 2021, to June 30, 2021. A total of 393 records of patients were selected by simple random sampling. Data was extracted from compiled data forms where available information was already tabulated. Data was entered and analyzed using SPSS version 25. The determinant factors associated with mortality among COVID-19 patients were identified using bivariate and multivariable logistic regression analysis. A statistical association was declared with multivariable logistic regression using a 95% confidence interval and a P-value of less than 0.05. The proportion of COVID-19 mortality among patients admitted to Eka Kotebe General Hospital was 8.1% (95% CI (5.4-10.8%)). Age >50 years [AOR = 7.91; 95% CI (2.34-25.70)], being male [AOR = 2.09; 95% CI (1.20-3.65)], having diabetes mellitus [AOR = 2.64; 95% CI (1.30-5.35)], having hypertension [AOR = 2.67; 95% CI (1.22-5.88)] and having chronic kidney disease [AOR = 12.04; 95% CI (4.03-14.22)] were determinant factors of COVID-19 mortality. The current study findings revealed that COVID-19 mortality was high among hospitalized COVID-19 patients. Furthermore, age, gender, diabetes mellitus, hypertension, and chronic kidney disease were discovered to be independent predictors of COVID-19 mortality. Therefore, older COVID-19 patients and those with established comorbidities such as hypertension, diabetes, and end-stage renal disease should receive comprehensive preventative efforts, including vaccination.